The safety and tolerability of oral AZD5069, a selective CXCR2 antagonist, in patients with moderate-to-severe COPD. (April 2015) - Kirsten, A.M.; Förster, K.; Radeczky, E.; Linnhoff, A.; Balint, B.; Watz, H.; Wray, H.; Salkeld, L.; Cullberg, M.; Larsson, B.
Abstract: Background: Chronic obstructive pulmonary disease (COPD) is characterized by neutrophil-dominated airway mucosal inflammation and elevated neutrophil counts in sputum and lung tissue. CXC chemokine receptor 2 (CXCR2) is predominantly expressed on neutrophils and mediates the migration of neutrophils to inflammatory sites. AZD5069 is a small molecule CXCR2 antagonist with the potential to inhibit neutrophil migration into the airways in patients with COPD. Methods: This 4-week, randomized, double-blind, placebo-controlled, parallel-group, multi-center, Phase IIa study evaluated the safety and tolerability of AZD5069 in patients with moderate-to-severe COPD (ClinicalTrials.gov identifier:NCT01233232 ). The pharmacokinetics and effect of AZD5069 on blood neutrophil counts were also assessed. Patients completed daily diary cards and attended weekly clinic visits for safety assessments. Results: 87 patients (mean FEV1 56% pred; mean age 64 years; 69% male) were randomized to receive placebo (n = 29), AZD5069 50 mg bid (n = 30) or AZD5069 80 mg bid (n = 28) for 4 weeks. AZD5069 was well tolerated with adverse events (AEs) reported in 9 (31%), 10 (33%) and 6 (21%) patients in the placebo, AZD5069 50 mg and AZD5069 80 mg groups, respectively. AEs were generally mild or moderate in severity. The incidence of infections, the most commonly reported AE, was similar across the three groups (17%, 17% and 11% of patients in the placebo, AZD5069 50 and 80 mg groups, respectively). Blood neutrophil counts decreased on average from baseline by 14–40% and 13–36% in the AZD5069 50 mg and 80 mg groups, respectively, and 4 patients discontinued from the study due to decreased neutrophil count, 3 in the AZD5069 50 mg group and 1 in the 80 mg group. The systemic exposure (AUC and Cmax ) of AZD5069 increased less than in proportion to the dose and there was a large overlap in the individual exposures between the two dose levels. Conclusions: AZD5069 was well tolerated overall in those patients who completed study treatment, with no increase in infection rates in either dosage group compared with placebo. Further studies with AZD5069 appear to be warranted.